Mistranslation in Candida albicans - Sousa, Diana Sofia Ortiga de (2018)
The genetic code establishes the rules that determine the transfer of genetic information from nucleic acids to proteins. The importance of the genetic code in genome decoding and its high conservation suggests that its evolution is highly restricted or even frozen. Despite this, various prokaryotic and eukaryotic genetic code alterations have been found, showing that the code is surprisingly flexible. For instance, the human pathogen Candida albicans contains an ambiguous tRNACAG that decodes a CUG codon as Ser (97%) and as Leu (3%). To further study ambiguity in other amino acid codons, we have engineered 8 mutant tRNASer that misincorporate Ser at 8 different codons belonging to distinct amino acids families (Glu, Arg, Asn, Cys, Phe, Gln, His and Pro) in Candida albicans. The wild-type tRNA was subjected to site-directed mutagenesis in order to change its anticodon to CUC, CCU, GUU, GCA, GAA, CUG, GUG and GGG. The tRNA stability, the cellular changes and the stress response of the resulting mistranslating strains were evaluated through northern blot analysis, cell transformation efficiency, growth rate and expression of a HSP104-GFP reporter system. A phenotypic screening probing various environmental stress conditions was performed in order to further characterize these strains. Experimental data suggest that these genetic code ambiguities affect fitness negatively in standard growth conditions and introduce growth advantages in presence of stress conditions. Thus, stress response triggered by codon ambiguity increase adaptation potential.